Effects of planting pattern and planting date of corn on agronomic traits of maize-bean intercropping systems - Sangoi, Luis; de Almeida, Milton Luiz (Pesquisa Agropecuaria Brasileira, 1993)
This experiment was carried out in Lages, SC, Brazil, with the purpose of evaluating the influence of planting pattern and planting date of corn (Zea mays L.) on grain yield and compounds of maize-bean (Phaseolus vulgaris L.) intercropping systems. Two planting dates of corn: one at the same day of bean and the other 18 days after bean sowing were tested. Four planting patterns were tested at each date of sowing: one, two, three and four plants per hill. The distance between two hills was 20, 40, 60 and 80 cm, for each planting pattern on grain yield of maize and bean. When the planting date of corn was delayed, bean yield was higher than the sowing of the crops was done at the same time. There was no effect of corn planting date on maize yield. The intercropping systems tested didn't differ in relation to the efficiency of land use (UET) and show greater values of UET than the sole cropping systems.
Keywords: Phaseolus vulgaris; Zea mays; grain yield; crop system